Implementation of Sustainable Development Goals to Makassar Zero Waste and Energy Source - Saleh, Haeruddin; Surya, Batara; Hamsina, H. (International Journal of Energy Economics and Policy, 2020)
The purpose of this research is to answer the problem and to apply the concept of waste management in Manggala subdistrict, the concept is the establishment of the waste school, waste bank, and 4R program assistance, to complete the waste Well-managed. The method of research that will be descriptive by describing factual and more accurate in seeing the reality and behavior of the population in the region as an object that becomes the research area so that the data can be explain the real conditions that exist in the field. The implementation of research in the district Manggala gave the idea that waste is very large and becomes a problem, with the implementation of the concept of waste management through the waste school than the public conscious, love the environment together and form Entrepreneurship based waste group so that waste can be reduced every day by 20 percent, through recycling can improve the community economy, thus the environment is awake and sustainable. Concept applied in Manggala district to become a pilot project so that Makassar city can reach zero waste. Keywords: Waste School; Waste Bank; Processing, Zero Waste, and Energy JEL Classifications: Q1, Q2, I3 DOI: https://doi.org/10.32479/ijeep.9453